Karakteristik Kimia dan Organoleptik Nugget Ikan Tuna (Thunnus sp.) dengan Penambahan Pasta Kenari (Canarium indicum L.) - Difinubun, Rati R; Mailoa, Meitycorfrida; Augustyn, Gelora H (Jurnal Agrosilvopasture-Tech, 2024)
Fish nuggets are one of the diversified fishery products. Groundfish meat is added with binding ingredients and seasonings, then steamed and molded. Tuna (Thunnus sp.) is a fish with high economic value and is relatively abundant in Indonesian seas. Walnuts (Canarium indicum L.) are one of the native Indonesian plants which are widely used as food. This study aimed to determine tuna nuggets' chemical and organoleptic characteristics by adding walnut paste. This study used a one-factor complete randomized design: walnut paste concentration with four treatment levels of 0%, 25%, 50%, and 75% with tri repeats. Observed variables include water, ash, fat, protein, carbohydrate content, hedonic tests, and hedonic quality of color, taste, aroma, and texture. The results showed that giving walnut paste affected fish nuggets' chemical and organoleptic properties. The water content of fish nuggets decreases, while the ash, fat, protein, and carbohydrate content increases with the addition of walnut paste concentration from the beginning of treatment, influencing the hedonic assessment and hedonic quality.